2014
DOI: 10.1083/jcb.201309092
|View full text |Cite
|
Sign up to set email alerts
|

Vinculin phosphorylation differentially regulates mechanotransduction at cell–cell and cell–matrix adhesions

Abstract: Vinculin phosphorylation on residue Y822 is necessary for cell stiffening in response to tension on cadherins but not integrins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
174
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(186 citation statements)
references
References 49 publications
10
174
1
1
Order By: Relevance
“…Abl kinases are also activated in response to E-cadherin and N-cadherin (Bays et al, 2014;Zandy et al, 2007). Active Abl kinases are required for both the maintenance and remodeling of cadherin-dependent adherens junctions (see poster).…”
Section: Structure Modular Domains and Enzymatic Regulation Of The Amentioning
confidence: 99%
See 1 more Smart Citation
“…Abl kinases are also activated in response to E-cadherin and N-cadherin (Bays et al, 2014;Zandy et al, 2007). Active Abl kinases are required for both the maintenance and remodeling of cadherin-dependent adherens junctions (see poster).…”
Section: Structure Modular Domains and Enzymatic Regulation Of The Amentioning
confidence: 99%
“…Simultaneous inactivation of both ABL1 and ABL2 disrupts adherens junctions in fibroblasts and epithelial cells (Li and Pendergast, 2011;Zandy et al, 2007). Recently, Abl kinases were shown to phosphorylate the actin-binding protein vinculin at epithelial cell-cell junctions, and this modification was required to promote E-cadherin-mediated adhesion and force transmission (Bays et al, 2014). Growth-factorinduced turnover of cadherin-based epithelial and endothelial cellcell junctions also requires Abl kinases.…”
Section: Structure Modular Domains and Enzymatic Regulation Of The Amentioning
confidence: 99%
“…DeMali and colleagues have demonstrated that applied force on E-cadherin increases the Abl-mediated phosphorylation of vinculin on tyrosine 822 (Y822) and allows vinculin to integrate into E-cadherin-based intercellular junctions (Bays et al, 2014). The degree of Y822-phosphorylated vinculin within adherens junctions then determines the extent to which cadherins transduce force.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation at position 822 by the kinase Abl is only required for E-cadherin-mediated force transmission and signaling in cell-cell contacts (Subauste et al, 2004), but not for force transmission through cell-ECM adhesions (Bays et al, 2014). By contrast, phosphorylation of vinculin at position 100 and 1065 by Src kinase affects cell spreading and wound repair (Zhang et al, 2004;Moese et al, 2007).…”
Section: Introductionmentioning
confidence: 99%